Prescription of oxygen concentrators for long term oxygen treatment: reassessment in one district. Issue 6655 (22nd October 1988) - Walshaw, M. J.; Lim, R.; Evans, C. C.; Hind, C. R.
Abstract : When oxygen concentrators became available on form FP10 in 1985 the Department of Health and Social Security issued clear guidelines for their prescription for long term treatment. Reassessment of those patients prescribed a concentrator in one district showed that 29 out of 61 patients did not fulfil these criteria. Furthermore, in only 28 cases was the daily use of the machine appropriate, though this did not reflect poor patient cooperation but was a result of inadequate prescribing instructions. In addition, 12 out of 54 patients continued to smoke. Overall, in only 18 of the 61 cases was both the prescription appropriate and the concentrator properly used. These results suggest a need for better cooperation between general practitioner and hospital in the initial assessment of patients for long term oxygen treatment and better education of both doctor and patient in the use of oxygen concentrators.